2020
DOI: 10.1103/physrevb.101.024109
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the origin of the magnetocaloric effects in substitutional Ni-Mn-Sb-Z(Z=Fe,Co,Cu) compounds: Insights from first-principles calculations

Abstract: Ni-Mn based ternary Heusler compounds have drawn attentions lately as significant magnetocaloric effects in some of them have been observed. Substitution of Ni and Mn by other 3d transition metals in controlled quantity have turned out to be successful in enhancing the effect and bring the operational temperatures closer to the room temperature. Using density functional theory calculations, in this work, we have systematically explored the roles of various factors such as site occupancies, magnetic interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Notably, it is not a unique instance, but has its counterpart. When Cu was introduced to Ni-rich Ni–Mn–X (X = In, Sn, Sb) alloys 20–22 or Mn-rich Mn–Ni–In/Sn alloys, 23,24 similar change tendencies of martensitic phase transition temperature and mechanical properties were experimentally observed. These results indicate that there exists a unified physical mechanism for martensitic phase transition and ductility in Cu-doped Ni–Mn-based FSMAs.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Notably, it is not a unique instance, but has its counterpart. When Cu was introduced to Ni-rich Ni–Mn–X (X = In, Sn, Sb) alloys 20–22 or Mn-rich Mn–Ni–In/Sn alloys, 23,24 similar change tendencies of martensitic phase transition temperature and mechanical properties were experimentally observed. These results indicate that there exists a unified physical mechanism for martensitic phase transition and ductility in Cu-doped Ni–Mn-based FSMAs.…”
Section: Introductionmentioning
confidence: 69%
“…, metallic or covalent bonding. 19,20,29,30 Previous studies verified their validity and they are still widely used to discuss the phase stability and mechanical properties of Ni–Mn-based Heusler alloys.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the increase in the martensite temperature is consistent with the decrease in elastic modulus. The relationship proposed by Ren and Otsuka [76] has been widely accepted for investigating the M s for TiNi-based [50,77,78], Cu−Al−Mn [79], and Ni-based [49,[80][81][82] systems. These studies [49,50,[77][78][79][80][81][82] have treated elastic modulus as one of the indicators to predict martensite temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in Cu-doped and/or alloyed Ni–Mn-based compounds have demonstrated its reliability. 32–34 The k -point mesh is 15 × 15 × 15 and all calculations are spin-polarized in this study. For reproducibility, pseudopotential configurations for Cu doped and/or alloyed Ni 2 MnTa compounds were selected as follows: Ni: Ni_80.otfg, Mn: Mn_80.otfg, Ta: Ta_80.otfg, and Cu: Cu_80.otfg.…”
Section: Computational Detailsmentioning
confidence: 99%